The Palk Strait project : a transit passage regime for a canal? - Mohd Hazmi Mohd Rusli (2012)
An Indian government project to dig an 83 km long canal to deepen the Palk Strait between Sri Lanka and the Indian sub-continent, raises the prospect of the Strait being opened to international traffic when completed. Will the transit passage regime apply in the Palk Strait to international maritime navigation?